Chemical looping of metal nitride catalysts: low-pressure ammonia synthesis for energy storage1. Issue 7 (15th July 2015) - Michalsky, R.; Avram, A. M.; Peterson, B. A.; Pfromm, P. H.; Peterson, A. A.
<x xml:space="preserve">Abstract</x> Design principles for reducible metal nitride catalysts are developed and demonstrated for ambient-pressure solar-driven N2 reduction into NH3.